Utilization Of Medical Plants In Hypertension Patients In Amparita Puskesmas, Tellu Limpoe District, Sidrap District - Rahmasiah, Rahmasiah; Sirajuddin, Washliaty; Harahap, Hastuti Nurmala Sari (Journal of Global Research in Public Health, 2021)
Background: Hypertension is the main risk factor for cardiovascular disease which is the highest cause of death, especially in Indonesia, for the treatment of hypertension, apart from using modern medicine, traditional medicine can also be used. In recent years, traditional medicine has become increasingly popular among the people as is the case with modern medicine. The high public interest in traditional medicine is also due to the low cost and easy to use itself. Purpose: to determine the utilization or use of medicinal plants in patients with hypertension at the Amparita Health Center, Tellu Limpoe District, Sidenreng Rappang Regency. Method: This type of research is a descriptive research. The sampling technique in this study used the purposive sampling technique. This research was carried out at the Amparita Health Center, Tellu Limpoe District, Sidenreng Rappang Regency from July to August 2019. Results: Medicinal plants used by people with hypertension were taken once a day, twice a day and 3 times a day. Conclusion: Medicinal plants that are used or used by people with hypertension in the working area of ​​the Amparita Health Center are soursop leaves, bay leaves, celery leaves, cucumbers, garlic, sweet starfruit, wuluh starfruit and noni fruit. The processing method is by boiling, blending and chewing or eating directly from the paper